Script concordance test to train clinical reasoning in speech therapy students - del Campo Rivas, Manuel Nibaldo; Silva-Ríos, Angélica Pilar (Revista de Investigación en Logopedia, 2023)
The script concordance test has been used in the training and evaluation of clinical reasoning (CR) as an innovative strategy in higher education. However, there is no evidence of its application in undergraduate speech therapy students. The aim of this research was to analyze the performance and perception of speech therapy students regarding the use of scripts. A pre-experimental and multicenter pilot was designed, complemented with three focus groups. Quantitative variables were summarized through means and standard deviation (SD). The comparison between groups was performed with Anova one way and Bonferroni post hoc test, with a significance level of p<.05. A content analysis through open coding, identification, and interpretation of categories of meaning was performed in the qualitative phase. Students had an average of 4.03 (SD= 0.35), with a significative increase in the CR through the course (p= 0.03). A positive perception was informed, and four families of meaning was described: clinical reasoning, opportunities for improvement, implementation of the strategy and teacher feedback. In conclusion, the use of scripts in speech therapy undergraduate students is feasible, increase the performance and supports the development of competence.